The Changing Academic Profession - Teichler, Ulrich. author. aut Link
X, 260 p.
Keywords: This book provides an overview on the major findings of a questionnaire survey of academic profession in international perspective. More than 25,000 professors and junior staff at universities and other institutions of higher education at almost 20 countries from all over the world provide information on their working situation, their views and activities. The study “The Changing Academic Profession” is the second major study of its kind, and changes of views and activities are presented through a comparison of the findings with those of the earlier study undertaken in the early 1990s. Major themes are the academics’ perception of their societal and institutional environments, the views on the major tasks of teaching, research and services, their professional preferences and actual activities, their career, their perceived influence and their overall job satisfaction. Emphasis is placed on the influence of recent changes in higher education: the internationalisation and globalisation, the increasing expectation to provide evidence of the relevance of academic work, and finally the growing power of management at higher education institutions. Overall, the academics surveyed show that worldwide discourses and trends in higher education put their mark on the academic profession, but differences by country continue to be noteworthy. Academics consider themselves to be more strongly exposed to mechanism of regulations, incentives and sanctions as well as various assessments than in the past; yet their own freedom, and responsibilities and influence shape their identity more strongly and are reflected in widespread professional satisfaction.